Geometry Learning through Extended Reality (XR): A Mini Review of Its Impacts, Implementation Challenges, and Future Developments - Hasanah, Nur Riski; Turmudi, Turmudi; Juandi, Dadang (Indonesian Journal of Education and Mathematical Science, 2026)
Extended Reality (XR) which includes AR, VR, MR, has become one of the important innovations in the development of mathematics learning media, especially in the field of geometry. This review aims to analyze the impact, implementation challenges, and future development directions of XR in geometry learning. A PRISMA-based systematic review was conducted with thematic analysis of literature from reputable international journals. The results of the study show that XR improves the effectiveness of learning and spatial thinking skills, student engagement, and learning motivation through interactive visualization and immersive learning experiences. However, negative impacts that need to be considered, include the dependence on technology, physiological and cognitive disorders, and heightened distraction that affects performance. Implementation challenges include limited infrastructure, teacher readiness, device access, costs, appropriate pedagogical design, and curriculum support for optimal XR integration.  Future developments suggest that XR holds strong transformative potential through integration with artificial intelligence (AI), adaptive learning systems, and educational metaverse environments. This study highlights the need for structured XR integration strategies and further research on long-term effectiveness and appropriate XR-based pedagogical design in mathematics learning, particularly geometry.